2013
DOI: 10.1103/physrevlett.110.055304
|View full text |Cite
|
Sign up to set email alerts
|

Bound States in a Quasi-Two-Dimensional Fermi Gas

Abstract: We consider the problem of N identical fermions of mass m " and one distinguishable particle of mass m # interacting via short-range interactions in a confined quasi-two-dimensional (quasi-2D) geometry. For N ¼ 2 and mass ratios m " =m # < 13:6, we find non-Efimov trimers that smoothly evolve from 2D to 3D. In the limit of strong 2D confinement, we show that the energy of the N þ 1 system can be approximated by an effective two-channel model. We use this approximation to solve the 3 þ 1 problem and we find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Kartavtsev and Malykh [41] found that universal (nonEfimov) fermionic states in 3D exist for mass ratios β [43] established that these states are continuously connected as confinement is increased. It is interesting to speculate whether the fermionic state that appears in 1D at β −1 = 1 (β −1 ≈ 1.170 in our calculation) is continuously connected to these universal trimer states in higher dimensions.…”
Section: Numerical Results For the Hhl Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Kartavtsev and Malykh [41] found that universal (nonEfimov) fermionic states in 3D exist for mass ratios β [43] established that these states are continuously connected as confinement is increased. It is interesting to speculate whether the fermionic state that appears in 1D at β −1 = 1 (β −1 ≈ 1.170 in our calculation) is continuously connected to these universal trimer states in higher dimensions.…”
Section: Numerical Results For the Hhl Systemmentioning
confidence: 99%
“…In 2D, Levinsen and Parish [43] found a critical mass ratio of β −1 ≈ 5.0. It is interesting to speculate whether these states are continuously connected to each other, and to the universal state that appears in these calculations at β −1 ≈ 2.0 for negativeparity fermions.…”
Section: A Adiabatic Equationsmentioning
confidence: 99%
“…[39,42] and demonstrated in a recent experiment [50]. Likewise, tetramers are predicted to exist in the ↑↑↑↓ problem [51,52] leading to an enhancement of the coefficient B 31 close to the critical mass ratio of 9.5 close to unitarity [52]. Indeed, the sign-change of the third virial coefficient at unitarity as a function of mass ratio [53] results from the resonantly enhanced p-wave channel becoming dominant.…”
Section: Fig 12mentioning
confidence: 99%
“…[4], implications of the quasi-2D nature of the gas seem to be unavoidable since the Fermi energy was larger than the level splitting in the tightly confined direction. The formalism constructed for molecule formation in quasi-2D systems [60] has recently been extended to study the polaron problem [64] and could be used to investigate the rf spectroscopy of quasi-2D systems.…”
Section: Discussionmentioning
confidence: 99%